Issues and Problems in Educational Surveillance and Proctoring Technologies - Parnther, Ceceilia; Eaton, Sarah Elaine (Canadian Perspectives on Academic Integrity, 2021)
Introduction. The increase of online course offerings due to COVID 19 has substantially increased eproctoring technology used to streamline classroom management and assessment. Faculty and students are increasingly concerned about the requirements of these systems. This presentation will: Explore the experiences of eproctoring internalized by college. Categorize this population's experiences and concerns in the context of eproctoring and surveillance. To do so, the following research questions are considered: How is eproctoring described in scholarly literature, social media, and student print media? What components of eproctoring surveillance are viewed as detrimental to student learning using these sources, and how do the impacted individuals describe these components? Research Methods. The presenters rapid review method is intended to provide timely decision-making information compared with standard systematic reviews. This method demonstrates the urgency and impact of eproctoring technologies on students. Institutions may use this information to make informed and holistic decisions on the specialized software they acquire and implement. For this study, the unit of analysis refers to unique student responses to eproctoring. The authors include (a) Peer-reviewed scholarly literature, (b) traditional print, (c) student print media defined as newspapers and magazines, (b) social media. Preliminary data (N = 20) describes e-proctoring surveillance technology as anxiety-provoking, intrusive, discriminatory, and adversarial. Stakeholders actively push back against e proctoring requirements and demand transparency, aligning with prior research on student privacy (Ifenthaler & Schumacher, 2016). Implications for Higher Education Policy or Practice. This study's results inform policymaking around assessment practices, standardizing expectations, and creating eproctoring standards and policies that center students' rights, personhood, and privacy that outweigh the need for convenient assessment.